Fugitive witnessing - Moratilla, Noel Christian A. (Družboslovne razprave, 2023)
Policies on migrant workers are characterised by competing frameworks of governance that do not necessarily protect migrants. Despite their vulnerability, however, migrant workers also possess agential capacities. Guided by the concept of “fugitive witnessing”, I discuss excerpts from the book “Bantay-Salakay: Anthology of Short Stories by Domestic Workers in Singapore, Hongkong and Taiwan” (Mga Bantay-Salakay: Antolohiya ng Maiikling Kuwento ng mga Indonesian Domestic Worker sa Singapore, Hongkong, at Taiwan), a collection of stories originally in Bahasa Indonesia and translated into Filipino. Specifically, I problematise how stories written by Indonesian domestic helpers reveal and negotiate varied aspects of migration. The paper concludes that stories of subaltern groups within the diaspora may serve as complex and discursive means to assess, interrogate and reform the contemporary phenomenon of labour mobilit
Keywords: diaspora; Indonesian migration; indonezijska migracija; Migracijsko delo; migrant stories; migrants; migrants' rights; Odrasli ubežniki; pravice migrantov; Priseljenci; zgodbe migrantov